Efecto de la disipacion viscosa en la condensacion de vapor sobrecalentado - Del Pozo, Franklin Villagomez (1971)
Studies viscous dissipation effects in the condensation heat transfer. Laminar film condensation of a superheated vapour, in the presence of a non-condensable gas, for forced flow over an horizontal, isothermal flat plate ata constant temperature, is analyzed. Condensation of pure vapour is treated as a particular case. The problem is formulated as an exact boundary layer solution. For numerical solution, steam as the condensing vapour and air as the noncondensable gas are considered. Heat transfer results are obtained for a wide range of values of the viscous dissipation parameter Ec (Eckert number). It is noted that the effect of viscous dissipation is to increase the temperature at the interface. Therefore, the effect of the viscous dissipation and that of superheating are similar. That is they produce an increase in the rate heat is transferred to the flat surface.